BP-cohomology of projective Stiefel manifolds. Issue 2 (April 2023) - Basu, Samik; Dasgupta, Debanil
Abstract : In this paper, we compute the BP -cohomology of complex projective Stiefel manifolds. The method involves the homotopy fixed point spectral sequence, and works for complex oriented cohomology theories. We also use these calculations and BP -operations to prove new results about equivariant maps between Stiefel manifolds.